PENDIDIKAN HUMANIS KH AHMAD DAHLAN, KI HAJAR DEWANTARA DAN PAULO FREIRE - Supala, Supala; Handayani, Dita; Rifai, Anwar (THORIQOTUNA: Jurnal Pendidikan Islam, 2020)
The background of this issue, there are cases of violence mostly by educators is still emerged, must be a serious concern concern, which is shows the low understanding of educators about the concept of humanist education, as exemplified by KH Ahmad Dahlan, Ki Hajar Dewantara or Paulo Friere as a famous figure of educators. The research is aimed to understand the humanist educational thought of a religious patterned (KH Ahmad Dahlan), nationalist (Ki Hajar Dewantara) and socialistic (Paulo Friere) style of humanist education. The method used in this research is a library research with a qualitative approach, by doing descriptive analysis and interpreting the data obtained. The results of this research shows that KH Ahmad Dahlan, Ki Hajar Dewantara and Paulo Freire have similarities in viewing humanist education, although they have a slightly differences in the use of terms and methods of field practical application.